The Effect of Xanthine Oxidase Inhibitors in the Prevention and Treatment of Stroke: A Systematic Review and Meta-Analysis - Lin Bai; Gerhard Litscher; Xiaoning Li (Journal of Cardiovascular Development and Disease)
Background: Xanthine oxidase inhibitors (XOIs) may help prevent stroke. However, heterogeneity can be found in the conclusions of different studies. The relevant evidence was summarized in this systematic review and meta-analysis to further clarify the role of XOIs in the prevention and treatment of stroke, with a focus on evaluating the effects of XOIs in primary and secondary prevention of stroke, acute stroke treatment, and reduction of post-stroke complications. Methods: Randomized controlled trials (RCTs) or cohort studies on the effect of XOIs in the prevention and treatment of stroke were searched in PubMed, EMBASE, and Cochrane Library from inception to 3 March 2024, along with hand searching. The analyses were carried out using Review Manager 5.4. Results: The analysis included 14 studies (115,579 patients). While XOIs did not significantly reduce the risk of stroke (RR: 0.89; 95% CI: 0.59–1.34), they improved post-stroke functional outcomes, with a reduction in the modified Rankin scale scores (mean difference: −0.6; 95% CI: −0.8 to −0.4), decreased intercellular adhesion molecule-1 levels (mean difference: −15.2 ng/mL; 95% CI: −22.3 to −8.1), improved augmentation index (AIx) by 4.2% (95% CI: 2.5–5.9%), reduced central blood pressure (mean reduction: 4.8 mmHg; 95% CI: 2.6–6.9), and delayed carotid intima-media thickness progression (mean difference: −0.05 mm/year; 95% CI: −0.08 to −0.02).